Resistency of White and Red Jabon Seedlings (Anthocephalus spp.) to Botryodiplodia theobromae (Pat.) Causing Dieback Disease UJI RESISTENSI BIBIT JABON PUTIH DAN MERAH (Anthocephalus spp.) TERHADAP Botryodiplodia theobromae (Pat.) PENYEBAB PENYAKIT MATI.. - Lola Adres Yanti; Achmad .; Nurul Khumaida (Jurnal Silvikultur Tropika, 2015)
Dieback disease on jabon seedlings is caused by Botryodiplodia theobromae decreased seedlings quality and economic benefits of nurseries. This is still sparse research for resistance test between white and red Jabon. This research aimed to test B. theobromae attacked with non wounded and wounded stem infection methods in Jabons and to obtain the most resistance of Jabons to B. theobromae attacked. The results showed that the disease incidence and the disease severity on both control of Jabon seedlings were 0% and 0%. But on treatment, white jabon seedlings non-wounded and wounded stem infection were 30% and 100%. For red jabon seedlings non-wounded and wounded stem infection were 80% and 100%. The disease severity on white jabon seedlings non-wounded and wounded stem infection were 12% and 62%. For red jabon seedlings non-wounded and wounded stem infection were 16% and 38%. The disease incidence on red Jabon seedlings were wider than white Jabon seedlings, but for the disease severity, white Jabon seedlings were worse than red Jabon seedlings. Botryodiplodia theobromae attacked non-wounded and wounded stem infection on Jabons.Key words: nursery, stem infection methods, the disease incidence, the disease severity